Strategize! experiential exercises in strategic management - Gopinath, C.; Siciliano, Julie 1949- (Australia South-Western, Cengage Learning, 2014)
Allows learners to try out the strategy models and concepts and get feedback regarding their understanding and application of strategic management theory. This book presents a number of experiential exercises and projects for use in and out of class.
PART I: UNDERSTANDING STRATEGIC MANAGEMENT. Strategy Session 1. Decision Making at the Strategic and Operational Level. Exercise: Innkeepers of America. Strategy Session 2. Understanding the Concept of Strategy. Exercise: How Do You Define Strategy? Strategy Session 3. Communicating Purpose Through Mission Statements. Exercise 1: How Well Do These Organizations Communicate Their Purpose? Exercise 2: Video-Create a Mission Statement for Caribou Coffee. Exercise 3: Video-Create a Mission Statement for Fossil, Inc. Strategy Session 4. The Board"s Role in Corporate Governance. Exercise: Translating the Board"s Role into Guidelines for Practice. Strategy Session 5. Viewing Strategy from the Stakeholder Perspective. Exercise: 1: Wal-Mart and Banking 30. Exercise 2: Role Playing Global Chemical Stakeholders" Interests and Power. PART II: DESIGNING STRATEGY. Strategy Session 6. Forces Affecting Competitive Strategy. Exercise: Intensity of Competition in the Casino Gambling Industry. Strategy Session 7. Generating a Plan of Action: SWOT (TOWS) Analysis. Exercise 1: An Action Plan for Robin Hood. Exercise 2: Video-Kropf Fruit Company-Future Strategy. Strategy Session 8. Developing Generic Strategy. Exercise 1: Choosing How to Compete in the Lodging Industry Exercise 2: Video-The Generic Strategy of Fossil, Inc. Strategy Session 9. Build Competitive Advantage. Exercise: Build Your Intended Strategy. Strategy Session 10. Viewing Corporate Strategy from the Core Competencies Perspective. Exercise: Corporate Strategy at Honda. Strategy Session 11. Global Strategic Alliances. Exercise: Renewing the General Motors-Toyota Alliance. Strategy Session 12. Identifying Transnational Strategies. Exercise: Global Operations of Bata Shoe and Nike. Strategy Session 13. Understanding Turnaround Management. Exercise: The Decline-Turnaround Sequence. Strategy Session 14. Scenario Planning: Innovative Approaches for the Future. Exercise: Develop Some Scenarios. PART III: IMPLEMENTING STRATEGY. Strategy Session 15. Succeeding in Strategy Formulation and Implementation. Exercise: Diagnosing Problems at Hewlett-Packard. Strategy Session 16. Structuring to Support Strategy. Exercise: Designing Organizational Structures for Club Ed. Strategy Session 17. Strategy Implementation Using the 7-S Model. Exercise: Transition at PeopleSoft. Strategy Session 18. Corporate Sustainability. Exercise: Video-BP"s Level of Corporate Sustainability. Strategy Session 19. Monitoring Strategy Implementation Through the Balanced Scorecard. Exercise: Everyone Knows the Score When a Major League Baseball Team Ties Performance to Its Mission. PART IV: INDUSTRY ANALYIS. Lodging Industry Profile. Template for Industry Survey. Assessing Strategic Performance Through Financial Analysis. Case Study 1 Strategic Alternatives at Mercury Telecom. Case Study 2 Caffeine Satisfaction: Rivalry Among the Coffee Shops. PART V: SEMESTER PROJECTS. Team Projects A and B. Project A: Comparing Two Organizations in the Same Industry. Project B: Identifying Strategic Issues at Local Business Organizations. MICA Method of Case Analysis and Discussion. References and Sources. Index.
International edition.
Includes bibliographical references (page 193-195) and index.
Keywords: Strategic planning -- Problems, exercises, etc